Exploring the Impact of a Sequential Lean Implementation Within a Micro-firm – a Socio-technical Perspective - Minshull, LK; Dehe, B; Kotcharin, S (Elsevier BV, 2022)
Lean implementations in large and medium-sized organisations are prominent in the literature. However, although small and micro-organisations significantly impact the countries’ economy, lean deployments in small and especially micro-firms are uncommon. This research aims to i) explore how a micro-manufacturing can initiate and develop a successful lean implementation and ii) establish the benefits and barriers from a socio-technical theory perspective. This action research is undertaken in a label manufacturer in the UK, where techniques such as 5S, single-minute exchange of dies, just in time, and total productive maintenance are implemented in sequence over six months to study the social and technical duality of lean. Both qualitative and quantitative data are collected to determine how the micro-organisation implements lean manufacturing and assess the extent to which it improves productivity, reduces lead time, and transforms culture. The results show that both performances are positively impacted and, more importantly, it has changed people’s behaviour.
Keywords: Lean implementation; Micro-organisation; Performance improvement; Socio-technical theory